2018
DOI: 10.1149/2.0961805jes
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Post Mortem Analysis of Solid Oxide Electrolyzer Cells after Long-Term Stack Operation

Abstract: A long-term test with a two-layer solid oxide electrolyzer stack was carried out for more than 20 000 hours. The stack was mainly operated in a furnace environment in electrolysis mode, with 50% humidification of H2 at 800 °C, a current density of -0.5 Acm -2 and steam conversion rate of 50%. After ~18 000 hours of operation in electrolysis mode, the voltage and area specific resistance degradation rates were ~0.6%/kh and 8.2%/kh, respectively. A detailed post mortem analysis of cells including ICP-OES and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…This statement must explain a large part of the higher experimental degradation rates measured for the Cell B compared to Cell A. Moreover, it is worth reminding that the destabilization of the oxygen electrode material accelerated under electrolysis current must also contribute to the overall cell degradation [14,21].…”
Section: Role Of Ni Depletion On Degradation mentioning
confidence: 97%
See 2 more Smart Citations
“…This statement must explain a large part of the higher experimental degradation rates measured for the Cell B compared to Cell A. Moreover, it is worth reminding that the destabilization of the oxygen electrode material accelerated under electrolysis current must also contribute to the overall cell degradation [14,21].…”
Section: Role Of Ni Depletion On Degradation mentioning
confidence: 97%
“…This latter phenomenon represents a significant contribution to the global cell degradation [19]. Indeed, it has been shown that the Ni-YSZ cermet is subjected under operation to a Ni agglomeration resulting in a phase coarsening and a migration changing the Ni distribution in the electrode [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reported degradation data are mostly hard to compare since cell concepts, materials and experimental conditions such as reactant flows, gas composition, conversion, voltage or current density strongly differ from one study to the other. Experimental investigations on the long-term stability of SOEC stacks are less available but highly required to identify and promote potential developments on cell, stack or system level [5,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, EIS deals with materials in which ionic conductivity dominates over electronic conductivity [2]. To date, this technique has been applied in a wide range of applications, such as supercapacitors [3][4][5], corrosion [6][7][8][9][10][11], solar cells [12][13][14], electrolysers [15][16][17][18], electrochemical sensors [19][20][21], batteries [22][23][24][25], and fuel cells [26][27][28][29], amongst others. Today, it is considered as one of the fundamental electrochemical techniques [30].…”
Section: Introductionmentioning
confidence: 99%